2021
DOI: 10.3390/polym13162737
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Retention Determination in Porous Media for Polymer Flooding in Unconsolidated Reservoir

Abstract: Polymer flooding is a well-established technique aimed at improved recovery factors from oilfields. Among the important parameters affecting the feasibility of a large deployment, polymer retention is one of the most critical since it directly impacts the oil bank delay and therefore the final economics of the project. This paper describes the work performed for the East-Messoyakhskoe oilfield located in Northern Siberia (Russia). A literature review was first performed to select the most appropriate methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…(2) mechanical entrapment due to the molecule size; and (3) hydrodynamic entrapment in unswept zones (Al-Hajri et al, 2018). Polymer retention can be minimized by selecting an agent that will be the most suitable for the reservoir conditions (Ilyasov et al, 2021). 3) Presence of clays.…”
Section: Introductionmentioning
confidence: 99%
“…(2) mechanical entrapment due to the molecule size; and (3) hydrodynamic entrapment in unswept zones (Al-Hajri et al, 2018). Polymer retention can be minimized by selecting an agent that will be the most suitable for the reservoir conditions (Ilyasov et al, 2021). 3) Presence of clays.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced oil recovery (EOR) technology such as water/polymer/CO 2 flooding has been widely adopted over several decades in the petroleum industry to enhance the hydrocarbon recovery rate [1,2]. The two major water-related operational challenges associated with EOR are mineral scale deposition and metal corrosion [3].…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al [ 21 ] and Gupta and Trushenski [ 22 ] found that the IAPV decreased when polymer concentrations increased. However, Ilyasov et al [ 23 ] stated that their IAPV results were strongly influenced by the increased polymer retention due to increased polymer concentrations.…”
Section: Introductionmentioning
confidence: 99%